THE HISTORY OF PILGRIMAGE TOURISM AND ITS ROLE IN THE FIELD OF TOURISM - Xasanova Nargiza Athamovna; Abilqosimov Asadbek Bahodir o‘g‘li (Web of Journals Publishing, 2024)
Pilgrimage tourism is currently a widespread tourism industry. Pilgrimage tourism is essentially the process of visiting places of pilgrimage. Pilgrimages are usually long journeys of days, weeks or even months for religious purposes. In this article, we will dwell on the description of pilgrimage tourism, its essence, and how important it is today.
Keywords: pilgrimage tourism, religious shrine, mausoleum, shrine.